Efficacy of novel thermomechanically treated reciprocating systems for gutta-percha removal from root canals obturated with warm vertical compaction - Cangul Keskin; Evren Sarıyılmaz; Duygu Hazal Güler (Tabriz University of Medical Sciences, 2018)
Background. The present study aimed to test the efficacy of novel reciprocating systems in terms of gutta-percha removal from root canals obturated with warm vertical compaction technique. Methods. Ninety straight-rooted maxillary incisors were enlarged with hand files up to a #50/02 apical size and obturated using warm vertical compaction technique. The specimens were divided into four groups according to the system used for removal of obturating material: Reciproc Blue, Reciproc, WaveOne Gold and hand instrumentation. The residual filling materials and time required for root canal removal were calculated. Statistical analyses were performed using one-way ANOVA and Tukey tests at 5% significance threshold. Results. There were no significant differences among Reciproc, Reciproc Blue and WaveOne Gold (P>0.05). The hand instrumentation group exhibited significantly more resisual root canal filling material (P<0.05). The time required for root canal filling removal was significantly shorter in the Reciproc group followed by WaveOne Gold, Reciproc Blue and hand instrumentation groups (P<0.05). Conclusion. Efficacy of Reciproc Blue, WaveOne Gold and Reciproc instruments for root canal filling removal were similar and superior to hand instrumentation.